2011
DOI: 10.1111/j.1471-0307.2011.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the texture of acidified sodium caseinate gels with added inulin using response surface methodology

Abstract: This work evaluated the effect of inulin concentration (0–6.0% w/w) on the mechanical properties and microstructure of gels composed of sodium caseinate (CN) (1.5–6.5% w/w) at pH 4.6. Inulin did not statistically affect the elastic modulus and rupture properties of the studied gels but affected the nonlinear mechanical behaviour. Samples with higher inulin concentrations (6% w/w) presented strain‐weakening deformation behaviour, whilst gels with lower inulin concentrations were strain hardening. The presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The author has noticed that the structure of whey-inulin gels was thicker. Furthermore, Picone, Maximo, Kuhn, Ros-Polski, and Cunha [ 53 ] claimed that samples with inulin and caseinate gels appeared to have slightly more closed pores than the pure protein samples. Compering the studies of Turgeon et al [ 54 ] with the studies conducted for the purposes of this publication, and by analyzing the SEM images, it was found that hydrogels with the addition of plant proteins did not show the phenomenon of thermodynamic incompatibility, in other words, no repulsion or lack of interaction between protein and inulin molecules were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The author has noticed that the structure of whey-inulin gels was thicker. Furthermore, Picone, Maximo, Kuhn, Ros-Polski, and Cunha [ 53 ] claimed that samples with inulin and caseinate gels appeared to have slightly more closed pores than the pure protein samples. Compering the studies of Turgeon et al [ 54 ] with the studies conducted for the purposes of this publication, and by analyzing the SEM images, it was found that hydrogels with the addition of plant proteins did not show the phenomenon of thermodynamic incompatibility, in other words, no repulsion or lack of interaction between protein and inulin molecules were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Picone et al . () reported that the presence of inulin in casein gels at concentrations of 0–6% (w/w) resulted in a more closed‐pore network. Gel deformability increased as sodium caseinate concentration was enhanced, reaching a maximum of 0.60 at 5.58% (w/w) of sodium caseinate, but it was not affected by inulin concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Such differences were associated to the goodness-of-fit of BST equation since Ebst values were quite similar to E values with the best BST fitting. Other authors Picone, Maximo, Kuhn, Ros-Polski, & Cunha, 2011;) also found that Ebst was different than E values obtained from the slope for the original raw data.…”
Section: Mechanical Propertiesmentioning
confidence: 89%